PENGARUH KOLABORASI DAN EVALUASI DALAM SUPPLY CHAIN PADA INVESTASI LINGKUNGAN DI LEVEL PRODUSEN (STUDI KASUS: PADA PERUSAHAAN FOOD INDUSTRY DI KOTA MEDAN) - Julita SE,M.Si; Mawardi Nur, SE (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2009)
This study aims to empirically testing the influence of collaborative activity between the factory with customers and suppliers on environmental investments at the level of producers in the allocation of Pollution Prevention and empirically test the influence of the evaluation activities of the factory with customers and suppliers on environmental investments in the allocation of producer dilevel Pollution Control and test empirically the influence of collaboration and evaluation activities of the factory with consumers and suppliers are allocated in the Pollution Prevention and Pollution Control jointly on environmental nvestasi producers dilevel. This study uses primary data to test hypotheses on the data collection methods of this research is to use survey methods, the research instrument in the form of a questionnaire distributed by way of coming each company according to the list of food industry companies in the city of Medan.Research results showed that overall the process of collaboration with customers and suppliers with consumers yng producers showed a positive impact on the environment nestasi form.Nevertheless, very real collaborative process occurs only on the supplier by the manufacturer.Whereas collaboration between consumers and producers are still a little place or in other words, the involvement of consumers in providing input or directly involved in efforts to improve the environment for investments is still very small producers. The process of evaluation both from consumers and suppliers to the producers still felt lacking. Even in the evaluation process that involved consumers virtually nothing, where both the industry biscuits, snacks and bakery can not find a significant influence. In the evaluation process, the real impact on the industry only biscuits and snack food industry, only affect the level of 10%. The process of collaboration and evaluation by consumers and suppliers to the producers as a whole can improve the investment environment in the food industry (Food Industry). Although the bakery industry both of these activities have not shown significant results on improving the investment environment.